Cardiac resynchronization therapy via left bundle branch pacing in heart failure with complete left bundle branch block: is the defibrillator needed? - Yang, Dandan; Ma, Qunchao; Zhu, Hong; Wang, Lihua; Xiang, Meixiang; Wang, Jian’an; Pan, Xiaohong (Frontiers in Cardiovascular Medicine, 2025)
AimsThis retrospective cohort study aimed to investigate the efficacy of dual-chamber left Bundle branch pacing (LBBP) as an alternative therapy for heart failure patients with complete left bundle branch block (CLBBB) and indications for defibrillator with cardiac resynchronization therapy (CRT-D).Methods34 patients met inclusion criteria were enrolled in the study. These criteria included a left ventricular ejection fraction (LVEF) of lower than 35%, a New York Heart Association functional class of II–IV, CLBBB meeting Strauss's criteria, intraventricular dyssynchrony, and confirmed correction of CLBBB during LBBP. Patients with ischemic cardiomyopathy, left ventricular noncompaction, significant late gadolinium enhancement (LGE) on cardiac magnetic resonance imaging (CMR), and indications for an implantable cardioverter-defibrillator (ICD) as secondary prevention were excluded.ResultsPost-LBBP, the LVEF improved from 31.1 ± 4.0% to 61.0 ± 6.0% (P < 0.001). All patients exhibited a super-response to LBBP cardiac resynchronization therapy, achieving complete improvement in cardiac function with a LVEF exceeding 50%. Septal-to-posterior wall motion delay (SPWMD) and systolic dyssynchrony index (SDI) were indicators of intraventricular synchrony, SPWMD decreased from 271.4 ± 76.4 ms to 42.2 ± 22.9 ms (P < 0.001), and SDI decreased from 12.5 ± 5.3% to 1.9 ± 1.0% after implantation (P < 0.001).ConclusionsHeart failure patients meeting the following criteria may be considered for dual-chamber pacing as an alternative to CRT-D, potentially avoiding the need for ICD implantation: (1) CLBBB meeting Strauss's criteria, (2) presence of intraventricular dyssynchrony on echocardiogram, (3) exclusion of secondary prevention ICD indications, (4) absence of evident LGE on CMR, and (5) successful correction of CLBBB during LBBP.